(untitled) (Bangladesh Journal of Zoology, 2015)
Proximate composition of chapila fish (Gudusia chapra) was determined using two different treatments of smoke-drying. In salt treated smoke-dried chapila (S-C), moisture, crude protein, lipid and ash contents were found 5.31%, 46.47%, 29.05% and 19.92% respectively. The same parameters were 6.77%, 45.24%, 30.52% and 18.71% respectively in case of salt-garlic treated smokedried chapila (S+G-C) fish. During storage at room temperature (26-320C), the percentage of moisture was increased significantly whereas crude protein, lipid and ash contents were decreased. The values of moisture (%) content were increased 9.91% (8th months) in S-C and 10.74 % (16th months) in S+G-C respectively. The values of protein (%) content were decreased 44.81% (8th months) in S-C and 42.66% (16th months) in S+G-C respectively. Values of fat and ash (%) content were decreased 28.55% and 18.01% (8th months) respectively in S-C and 28.75% and 17.34% (16th months) respectively in S+G-C. The overall study showed that the smoke cured fish treated with salt-garlic had longer shelf life and found better for preservation. Bangladesh J. Zool. 42(2): 205-209, 2014